Association between Elevated Mean Corpuscular Volume and C-reactive protein in Patients with Rheumatoid Arthritis. Issue 5 (2018) - Kuroda, Takeshi; Tanabe, Naohito; Sato, Hiroe; Kobayashi, Daisuke; Nakatsue, Takeshi; Wada, Yoko; Nakano, Masaaki; Narita, Ichiei
No abstract available